EUPD: A Case Study Highlighting the High Stakes of First Impressions and the Dangers of Groupthink - Aisha Duale (BJPsych Open)
Aims: Emotionally unstable personality disorder (EUPD) is a mental disorder that can be one of the most misunderstood diagnoses. It is a controversial and stigmatised condition among healthcare professionals which may lead to sub-standard levels of care and sub-therapeutic patient experience.